Modification of a single-molecule AFM probe with highly defined surface functionality - Long, Fei; Cao, Bin; Khanal, Ashok; Fang, Shiyue; Shahbazian-Yassar, Reza (Beilstein Journal of Nanotechnology, 2014)
Single-molecule force spectroscopy with an atomic force microscope has been widely used to study inter- and intramolecular interactions. To obtain data consistent with single molecular events, a well-defined method is critical to limit the number of molecules at the apex of an AFM probe to one or to a few. In this paper, we demonstrate an easy method for single-molecule probe modification by using the Cu-catalyzed alkyne–azide cycloaddition reaction. Excess terminal alkynes were covalently attached to the probe, and a bi-functional molecule containing an azide at one end and a carboxylic acid at the other was dissolved in the reaction solution. By simply contacting the probe and the Cu substrate, controlled carboxylation on the probe apex could be achieved, since the ‘click’ reaction requires the co-exist of alkyne, azide and Cu(I). The finite contact area would result in a highly defined surface functionality of the probe down to single molecule level with high reproducibility.
Keywords: atomic force microscopy; click reaction; force spectroscopy; single molecule modification